2022
DOI: 10.3389/fpls.2022.835282
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Transfer-DNA-Free Base-Edited Citrus Plants

Abstract: To recover transgenic citrus plants in the most efficient manner, the use of selection marker genes is essential. In this work, it was shown that the mutated forms of the acetolactate synthase (ALS) gene in combination with the herbicide selection agent imazapyr (IMZ) added to the selection medium may be used to achieve this goal. This approach enables the development of cisgenic regenerants, namely, plants without the incorporation of those bacterial genes currently employed for transgenic selection, and addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In citrus, the few studies that have applied CRISPR/Cas9 technology used the Golden Gate strategy. This approach has been adopted to introduce resistance to Xanthomonas citri (the causal agent of citrus canker disease) to susceptible citrus species ( Jia et al., 2016 ; Jia et al., 2017 ), to produce a double thorn phenotype in ‘Carrizo’ citrange ( Zhang et al., 2021b ), and to induce resistance against the herbicide imazapyr ( Alquézar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In citrus, the few studies that have applied CRISPR/Cas9 technology used the Golden Gate strategy. This approach has been adopted to introduce resistance to Xanthomonas citri (the causal agent of citrus canker disease) to susceptible citrus species ( Jia et al., 2016 ; Jia et al., 2017 ), to produce a double thorn phenotype in ‘Carrizo’ citrange ( Zhang et al., 2021b ), and to induce resistance against the herbicide imazapyr ( Alquézar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We first investigated if we could obtain transgene-free, gene-edited tomato in the T0 generation by base-editing SlALS1 (Solyc03g044330) alone. Previous studies suggested such a possibility, but the putative transgene-free plants were not confirmed by whole genome sequencing 10,15,28 . Here, we constructed the CBE-Cas12a-GFP-SlALS1 construct to edit the SlALS1 gene using CBE to target the proline residue at position 186 (Pro186) (Fig.…”
Section: Als Gene and Gene Of Interestmentioning
confidence: 94%
“…In Carrizo citrange, a genome-editing approach was developed to produce a double thorn phenotype [ 80 ]. Very recently, Alquézar and colleagues [ 81 ] induced through base editing resistance against the herbicide selection agent imazapyr, bypassing the limitations of the presence of the transgene for the selection and obtaining transgene free plants.…”
Section: Improving Citrus Fruit Quality By Ngt Approaches—the ...mentioning
confidence: 99%